The Role of Pericytes in Regulation of Innate and Adaptive Immunity - Siarhei A. Dabravolski; Elena R. Andreeva; Ilya I. Eremin; Alexander M. Markin; Irina I. Nadelyaeva; Alexander N. Orekhov; Alexandra A. Melnichenko (Biomedicines, 2023)
Pericytes are perivascular multipotent cells wrapping microvascular capillaries, where they support vasculature functioning, participate in tissue regeneration, and regulate blood flow. However, recent evidence suggests that in addition to traditionally credited structural function, pericytes also manifest immune properties. In this review, we summarise recent data regarding pericytes’ response to different pro-inflammatory stimuli and their involvement in innate immune responses through expression of pattern-recognition receptors. Moreover, pericytes express various adhesion molecules, thus regulating trafficking of immune cells across vessel walls. Additionally, the role of pericytes in modulation of adaptive immunity is discussed. Finally, recent reports have suggested that the interaction with cancer cells evokes immunosuppression function in pericytes, thus facilitating immune evasion and facilitating cancer proliferation and metastasis. However, such complex and multi-faceted cross-talks of pericytes with immune cells also suggest a number of potential pericyte-based therapeutic methods and techniques for cancer immunotherapy and treatment of autoimmune and auto-inflammatory disorders.